Anti-proliferative, apoptotic and signal transduction effects of hesperidin in non-small cell lung cancer cells - Çinçin, Zeynep Birsu; Ünlü, Miray; Kıran, Bayram; Bireller, Elif Sinem; Baran, Yusuf; Çakmakoğlu, Bedia (Springer Science and Business Media LLC, 2015)
Hesperidin, a glycoside flavonoid, is thought to act as an anti-cancer agent, since it has been found to exhibit both pro-apoptotic and anti-proliferative effects in several cancer cell types. The mechanisms underlying hesperidin-induced growth arrest and apoptosis are, however, not well understood. Here, we aimed to investigate the anti-proliferative and apoptotic effects of hesperidin on non-small cell lung cancer (NSCLC) cells and to investigate the mechanisms involved.The anti-proliferative and apoptotic effects of hesperidin on two NSCLC-derived cell lines, A549 and NCI-H358, were determined using a WST-1 colorimetric assay, a LDH cytotoxicity assay, a Cell Death Detection assay, an AnnexinV-FITC assay, a caspase-3 assay and a JC-1 assay, respectively, all in a time- and dose-dependent manner. As a control, non-cancerous MRC-5 lung fibroblasts were included. Changes in whole genome gene expression profiles were assessed using an Illumina Human HT-12v4 beadchip microarray platform, and subsequent data analyses were performed using an Illumina Genome Studio and Ingenuity Pathway Analyser (IPA).We found that after hesperidin treatment, A549 and NCI-H358 cells exhibited decreasing cell proliferation and increasing caspase-3 and other apoptosis-related activities, in conjunction with decreasing mitochondrial membrane potential activities, in a dose- and time-dependent manner. Through a GO analysis, by which changes in gene expression profiles were compared, we found that the FGF and NF-κB signal transduction pathways were most significantly affected in the hesperidin treated NCI-H358 and A549 NSCLC cells.Our results indicate that hesperidin elicits an in vitro growth inhibitory effect on NSCLC cells by modulating immune response-related pathways that affect apoptosis. When confirmed in vivo, hesperidin may serve as a novel anti-proliferative agent for non-small cell lung cancer.
Keywords: Lung Neoplasms; Hesperidin; Antineoplastic Agents; Apoptosis; Enzyme-Linked Immunosorbent Assay; Gene expression profile; Anti-proliferative effect; Non-small cell lung cancer; Carcinoma, Non-Small-Cell Lung; Cell Line, Tumor; Humans; Transcriptome; Cell Proliferation; Oligonucleotide Array Sequence Analysis; Signal Transduction; 7. Clean energy; 3. Good health